2013
DOI: 10.1002/elps.201200645
|View full text |Cite
|
Sign up to set email alerts
|

Determination of α‐hydroxy acids and their enantiomers in fruit juices by ligand exchange CE with a dual central metal ion system

Abstract: The content of α-hydroxy acids and their enantiomers can be used to distinguish authentic and adulterated fruit juices. Here, we investigated the use of ligand exchange CE with two kinds of central metal ion in a BGE for the simultaneous determination of enantiomers of dl-malic, dl-tartaric and dl-isocitric acids, and citric acid. Ligand exchange CE with 100 mM d-quinic acid as a chiral selector ligand and 10 mM Cu(II) ion as a central metal ion could enantioseparate dl-tartaric acid but not dl-malic acid or d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The use of chiral metal complexes for enantioseparation following the chiral ligand exchange principle provides high selectivity of chiral molecules, and following this idea, d ‐isocitric, l ‐isocitric acid, and citric acids were separated using a ligand exchange CE method with Ni(II)‐ d ‐quinic acid system. Following a similar approach, but with different ligand exchange (namely, Sc(III)/Cu(II)‐ d ‐quinic acid system), enantiomers of d / l ‐malic, d / l ‐tartaric, and d / l ‐isocitric acids, as well as and citric acid, were analyzed . The content of these α‐hydroxy acids enantiomers was also used to distinguish authentic and adulterated fruit juices.…”
Section: Chiral Analysis Of Food Compoundsmentioning
confidence: 99%
“…The use of chiral metal complexes for enantioseparation following the chiral ligand exchange principle provides high selectivity of chiral molecules, and following this idea, d ‐isocitric, l ‐isocitric acid, and citric acids were separated using a ligand exchange CE method with Ni(II)‐ d ‐quinic acid system. Following a similar approach, but with different ligand exchange (namely, Sc(III)/Cu(II)‐ d ‐quinic acid system), enantiomers of d / l ‐malic, d / l ‐tartaric, and d / l ‐isocitric acids, as well as and citric acid, were analyzed . The content of these α‐hydroxy acids enantiomers was also used to distinguish authentic and adulterated fruit juices.…”
Section: Chiral Analysis Of Food Compoundsmentioning
confidence: 99%
“…As observed in Table 1, LODs and LOQs ranged from 0.1 to 2.5 lg mL À1 and from 0.3 to 8.3 lg mL À1 , respectively. These values were lower than others previously published in literature for CZE methods (Kodama et al, 2013;Saavedra et al, 2000), although were higher than those reported using a Waters Capillary Ion analysis system at unusual short wavelength UV detection (185 nm) (Mato et al, 2006). Peak identification was performed by comparing migration times with those of the standards, and when necessary also by spiking the samples with the standards.…”
Section: Performance Characteristics Of the Cze Methodsmentioning
confidence: 55%
“…Another important group of chiral compounds related to food and beverage production are organic acids . These constituents (mainly present in the nature as single enantiomers) are responsible for a unique bouquet of wine, sake, cognac, juices, etc.…”
Section: First Fascinationsmentioning
confidence: 99%